1995
DOI: 10.1136/hrt.74.6.584
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme gene deletion allele is independently and strongly associated with coronary atherosclerosis and myocardial infarction.

Abstract: ACE deletion polymorphism is strongly and independently associated with coronary atherosclerosis and, to a lesser extent, with myocardial infarction. As such, the results are analogous to what has already been reported in French white, Japanese, and Welsh coronary patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 33 publications
2
43
1
3
Order By: Relevance
“…Recently, the interest in the ACE gene has increased after the reports that the homozygosity for the short allele (DD) is significantly more frequent in patients with coronary artery disease, 16 left ventricular hypertrophy, 24,25 hyperglycemia, 17 and dilated cardiomyopathy.…”
Section: Ace Gene Polymorphism and Cardiovascular Diseasesmentioning
confidence: 99%
“…Recently, the interest in the ACE gene has increased after the reports that the homozygosity for the short allele (DD) is significantly more frequent in patients with coronary artery disease, 16 left ventricular hypertrophy, 24,25 hyperglycemia, 17 and dilated cardiomyopathy.…”
Section: Ace Gene Polymorphism and Cardiovascular Diseasesmentioning
confidence: 99%
“…The same allele is known to be associated with risk of myocardial infarction at a young age, ischemic heart dis ease, etc. [10,23]. It can be suggested that the D/D geno type in placentae results in an increase of placental infarc tions and partial detachment of the placenta, and thus it could contribute to abnormalities of blood circulation in the placenta and to development of PI.…”
Section: Discussionmentioning
confidence: 99%
“…The I allele is associated with decreased ACE production compared to the D allele. An association of the D allele of with cardiovascular disease, in particular, with hypertension [22,23] and with some kinds of preeclampsia [24], has been reported. Since ACE is responsible for processes of vasoconstriction and vaso dilatation in placental tissue, it is logical to assume an association between its allelic variants and development of PI.…”
Section: Discussionmentioning
confidence: 99%
“…An insertion/deletion (I/D) polymorphism in intron 16 of the ACE gene on chromosome 17q23 has been identified resulting in three genotypes: homozygous DD, II and heterozygous ID [12]. A previous study of Tiret et al [13] found, that I/D polymorphism of the ACE gene is associated with ACE level, and that subjects who carry the I allele have a lower ACE level than subjects bearing the D allele.…”
Section: Introductionmentioning
confidence: 99%